REPRESENTASI SOSIAL TENTANG GANGGUAN JIWA PADA MASYARAKAT YANG INGIN MENCARI BANTUAN PSIKOLOGIS FORMAL (STUDI PADA MASYARAKAT BANTEN YANG RELATIF MODERN) - Prawiro, Ferdinand; Vereen, Agnes (Atma Jaya Catholic University of Indonesia, 2024)
Banten is one of the provinces that ranks first in health centers that organize mental health efforts. In Banten Province, the prevalence of patients with mental disorders who received treatment and were not abandoned was only 32.16%. With adequate knowledge and access to mental health services, there is no behavior to seek formal psychological help in there. This study aims to understand the meaning of mental disorders in Bantenese society using social representation theory with a structural approach and divided into two stages. The first stage aims to find the attributes of social representations of mental disorders using the word association method. There were 172 participants who participated in the first stage with a total of 929 responses. The categorization process was carried out, and 36 categories were obtained. Content analysis resulted in a Cohen's Kappa value of .588. The second stage aims to map the central core and peripheral attributes using the double denial technique. Results from 181 participants were tested with chi-square goodness of fit expected frequency. The social representation of mental illness in Banten society includes 17 attributes, 12 attributes of central core elements, and five attributes of peripheral elements. The results showed that Banten people have sufficient knowledge related to mental illness and sources of help. However, people still have negative views, concerns, cost considerations, feelings of helplessness, and confidentiality issues. Psychoeducation can be recommended as an intervention to increase public knowledge and shake abnormal and crazy attributes in peripheral elements.